Walking With Our Sisters: une commemoration artistique pour le feminicide autochtone, en marche vers la decolonisation - Bruneau, Julie (Recherches Feministes, 2017)
In reaction to the indigenous femicide in Canada, and to the inaction of the canadian government, the victim's relatives and grassroots indigenous women groups created various memorials. The author focuses on the commemorative art installation Walking With Our Sisters, project of the Métis artist Christi Belcourt. Thus, the author led a field survey, to better understand if it was an empowering experience for the women participants. She will also question the definition of western feminism, in contrast with indigenous feminism.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; art contemporain; artistes autochtones; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; femmes* artistes; féminicide; féminisme autochtone; féminisme décolonial; histoire et politique; intersectionnalité; militance; mémoire; mémorial; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; thématiques; violences